The Effect of Combination of Coconut Water and Sugarcane Water on Freshness Duration and Solution Absorption In Cut Chrysanthemums - Ipah Budi Minarti; Muhammad Anas Dzakiy; Siti - Muthoharoh (Advance Sustainable Science Engineering and Technology, 2023)
Indonesia has fertile natural conditions, providing great potential for developing horticultural commodities, one of which is ornamental plants. Chrysanthemum is an ornamental plant that has high economic value and is in high demand, so it must be balanced with the quality and quantity of the flower itself. Chrysanthemum flowers are very susceptible to physical damage after harvesting. The purpose of this study was to see the effect of giving a combination of coconut air and sugarcane air on freshness and absorption of cut chrysanthemum solution. This study used a completely randomized design (CRD) using 1 factor with 4 treatments with 3 replications.P0: 1 liter water (control), P1: 200 ml / l coconut water + 25 ml / l sugarcane juice + 775 ml air, P2: 400 ml / l coconut water + 35 ml / l sugarcane juice + 565 ml air P3: Coconut water 600 ml / l + 45 ml / l sugarcane juice + 355 ml air. Research data on the shelf life of hedge flowers were good and the solution was most absorbed in the P1 treatment with a combination of 200 mL / L coconut water and 25 mL / L sugarcane water with flower freshness reaching 13.3 days. and the absorbed solution was 66.67. Based on the research, it can be denied that there is an effect and interaction of coconut water and sugarcane juice on the freshness and absorption time of the cut chrysanthemum solution.